Kommunikation under Ankarhantering - Nyckeln till en gemensam information - Nordholm, Victor; Orvefors, Petter (My University, 2017)
The offshore industry is a demanding business where all involving parts need to fulfill high safety standards, particularly in the anchor handling vessels. Due to the high risk of working close to an offshore installation with very exposed crewmembers on deck. The main tool used to prevent onboard or operational accidents is communication, both internal and external. We have chosen to examine how the organization onboard an anchor handling vessel deals with the communication aspect in regards to preventing accidents and how the different departments onboard communicates. The method used was grounded theory based on semi-structured interviews (Denscombe, 2009) with six onboard experienced participants. The interviews were then transcribed and analyzed using recording equipment. The result showed that many of the problems we anticipated in the beginning of this study was not a big issue for those who work on board. The main problem described by the participants was the language difficulties. Due to the fact that in today´s North Sea based offshore business there are many different nationalities, even though it is mainly from Scandinavian countries the language differences is the main factor in bad communication and often the cause of misunderstandings onboard.
Keywords: Transport; Farkostteknik; Transport; Vehicle Engineering